- - Bustos Domínguez, Reinaldo (Acta Bioethica, 2000)
The paper presents David Le Breton's contribution to the anthropology of pain, as a proposal for a better understanding of the necessity of a more comprehensive medical practice, since more often than not, it is restricted to an empirical and positivist approach leading to intervene on diseases as if they were mere biological realities. On the contrary, the anthropological analysis of pain takes us to consider illness not only as the characterization of clinical signs, but also as a syndrome of lived experiences, loaded with significance, interpretations and explanations influenced by culture and personal subjectivity.